Pelestarian Sumberdaya Budaya Dalam Bingkai Otonomi Khusus Papua (STUDI KASUS CRM PAPUA) - Hari Suroto (BALAI ARKEOLOGI PAPUA, 2009)
The influence of globalization has been seriously threat for the endurance whether tangible or intangible culture now days. It is surely needed to find a concept to preserve the Papua’s culture so that it can’t be swept away. If it doesn’t work, the next generation of Papua will lose their basic culture because of globalization and modernism. Until now, the people and provincial government didn’t give a full attention to the cultural resources. However, Papua’s culture can be a high potential culture. So that the way to advantage and developed the culture resources must be aim to preservation.